(untitled) (Acta Scientiarum. Health Sciences, 2012)
Household Survey, a cross-sectional study aimed to describe the quality of life and functional capacity of elderly people with a history of stroke and compare the scores of quality of life with the number of functional disability. Data were collected at home, with the semi-structured instruments, WHOQOL-BREF and WHOQOL-OLD. Descriptive analysis was performed, as well as ANOVA and Tukey-F test (p < 0.05). Most individuals are males (53.3%), aged 70 â”œ 80 years old (45.6%), married (57.8%), 4 â”œ 8 years of study (36.7%) and income of a minimum wage (66.7%). The activities of daily living most affected were: cutting toenails and walk up and down stairs. The highest scores of quality of life were: the social relationships and the facet death and dying. The lowest scores were related to the physical domain and autonomy. The highest number of functional disability was associated with lower scores for physical and psychological domains and on the facets of autonomy and social participation. The elderly people with stroke have their functional status impaired, which affects their quality of life in aspects related to mobility, body image, decision-making capacity and living in the community.